A capsaicin-sensitive inhibitory reflex from the colon to mesenteric arteries in the guinea-pig. - Meehan, A G (1992)
1. The present in vitro study examined the effect of distension of the distal colon on membrane potential in the inferior mesenteric artery of the guinea-pig. 2. Distension of the distal colon up to an intraluminal pressure of 25 cmH2O induced a hyperpolarization in the inferior mesenteric artery. The average amplitude of hyperpolarizations induced by 2 min distensions of the colon was 3 mV and their average duration was 268 s. 3. Distension-induced hyperpolarizations (DIHs) were abolished in the presence of tetrodotoxin or a low-Ca2+ (0.5 mM) superfusion solution. 4. Superfusion of capsaicin (10 microM) induced slow hyperpolarizing responses in mesenteric arteries. Following application of capsaicin (10 microM), DIHs were abolished. 5. These findings provide strong evidence that mesenteric arteries receive an inhibitory, capsaicin-sensitive sensory innervation from the distal colon which is activated during periods of colon distension to induce hyperpolarization of the arterial smooth muscle. This extramural inhibitory reflex pathway may play a physiological role in co-ordinating mesenteric blood flow with changes in gut motility.